Application of a porphyrin conjugated organic polymer in lithium ion batteries
By using porphyrin-conjugated organic polymer as the positive electrode material in lithium-ion batteries, the problems of high solubility and low conductivity of existing organic positive electrode materials are solved, and the high discharge capacity and long cycle life of the battery are achieved.
Patent Information
- Application Number
- CN202411500308.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing organic positive electrode materials have high solubility and low electron conductivity in lithium-ion batteries, resulting in low battery discharge capacity and short cycle life.
Porphyrin-conjugated organic polymer is used as the positive electrode active material, and the electrochemical performance is improved through its unique advantages of insolubleness, high conductivity, multi-electrochemical reaction sites and structural stability.
Excellent electrochemical performance of lithium-ion batteries is achieved, such as H2BCPP-COP maintaining a high discharge specific capacity and capacity retention rate after high cycle times.
Smart Images

Figure CN119008941B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to the application of a porphyrin conjugated organic polymer in a lithium ion battery. Background Art
[0002] Energy has promoted the development of science and technology, and at the same time, the progress of science and technology has also promoted the rational use of energy. People have reduced the rough use of fossil fuels and increased the demand for clean energy and renewable energy. A series of renewable energy sources such as nuclear energy, solar energy, and wind energy can be converted into electrical energy for transportation and storage. Among secondary energy storage batteries, lithium-ion batteries have been rapidly commercialized due to their excellent comprehensive performance such as good cycle performance, high energy density, and low commercial cost, and have been widely used in 3C electronic consumer devices, new energy electric vehicles and other fields. At present, most of the positive electrode materials used in commercial lithium-ion batteries are metal oxides and polyanion salts, among which representative positive electrode materials are LiFePO4, LiMn2O4, LiCoO2, etc. The above materials have become the key positive electrode materials in the field of electrochemical energy storage due to their advantages such as low price, high theoretical capacity, and good stability. However, with the popularization of lithium-ion batteries, the non-renewable mineral resources and the environmental pollution caused by the Co element have brought challenges to the development of sustainable secondary batteries. Therefore, the development of the next generation of sustainable high-performance energy storage electrode materials has great application potential.
[0003] The huge development potential of organic cathode materials lies in their advantages of resource sustainability, low carbon footprint, and high theoretical specific capacity. Organic cathode materials are composed of light elements such as C, H, N, and S. They not only have high theoretical capacity, but also conform to the concept of green environmental protection and sustainable development. However, the high solubility of organic cathode materials in electrolytes and the poor intrinsic electronic conductivity have severely restricted their development and application. Organic polymer cathode materials formed by polymerization reactions can effectively overcome the problems faced by the above-mentioned organic cathode materials and have attracted widespread attention to organic polymer cathode materials.
[0004] The conjugated macrocyclic structure of the porphyrin molecule itself is conducive to the rapid excitation and transfer of electrons. Porphyrins in chlorophyll can capture visible light and achieve reversible conversion of light energy, electrical energy and chemical energy. Porphyrin compounds in hemoglobin also assume the important function of electron transfer. In addition, organic cathode materials based on porphyrin have pseudocapacitive properties similar to supercapacitors due to their ability to quickly transfer electrons. Porphyrins with suitable functional groups can form polymers, covalent organic frameworks, metal-organic frameworks and other porphyrin polymer cathode materials through a series of strategies such as in situ electropolymerization, chemical polymerization, and metal coordination self-assembly. These materials usually have unique advantages such as poor solubility, high conductivity, multiple electrochemical reaction sites, and stable structure. Therefore, porphyrin polymer cathode materials have potential application value as new organic electrode materials in the field of electrochemical energy storage. Summary of the invention
[0005] In order to solve the problems of high solubility and low electronic conductivity of existing organic positive electrode materials, which lead to low battery discharge capacity and short cycle life, the present invention provides an application of a porphyrin conjugated organic polymer in a lithium ion battery. The porphyrin conjugated organic polymer is used as a positive electrode active material, which has the unique advantages of poor solubility, high conductivity, multiple electrochemical reaction sites and stable structure, and thus has excellent electrochemical properties.
[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0007] A porphyrin conjugated organic polymer is used in a lithium ion battery. The porphyrin conjugated organic polymer is used as a positive electrode active material to prepare a positive electrode material for a lithium ion battery. The general structural formula of the porphyrin conjugated organic polymer is shown in formula (I):
[0008]
[0009] Formula (I)
[0010] Among them, Ar is selected from , , One of: X is selected from O, N, S.
[0011] Furthermore, the degree of polymerization n in the formula (I) ranges from 8 to 2000.
[0012] Furthermore, the porphyrin conjugated organic polymer is used as the positive electrode active material, and is fully and evenly ground with a conductive agent and a binder in a solvent to obtain a positive electrode slurry, which is then applied to a current collector and used as a positive electrode after vacuum drying. The battery is then assembled with a negative electrode, an electrolyte, and a separator in an argon atmosphere, wherein the negative electrode is a metal lithium sheet.
[0013] Furthermore, in the positive electrode slurry, the content of the porphyrin conjugated organic polymer is 40-90wt%, the content of the conductive agent is 5-60wt%, and the content of the binder is 5-10wt%.
[0014] Furthermore, the conductive agent is one of conductive graphite, conductive carbon black, carbon nanotubes and graphene; the binder is one of polytetrafluoroethylene, sodium carboxymethyl cellulose, polyvinylidene fluoride and polyurethane; the solvent is N-methylpyrrolidone; and the current collector is one of stainless steel foil, molybdenum foil, aluminum foil, copper foil and nickel foil.
[0015] Furthermore, the electrolyte is one of LiPF6, LiTFSI, LiFSI, LiClO4, and LiBOB.
[0016] The present invention has the following beneficial effects:
[0017] The organic positive electrode materials used in organic rechargeable secondary batteries in the prior art have the problems of high solubility and low electronic conductivity, which leads to low battery discharge capacity and short cycle life. The present invention introduces porphyrin conjugated organic polymers as positive electrode active materials for preparing positive electrode materials for lithium ion batteries, which have the unique advantages of poor solubility, high conductivity, multiple electrochemical reaction sites and stable structure, and thus have excellent electrochemical properties. For example, H2BCPP-COP has a high electrochemical performance at 2A g -1 After 7500 cycles, the discharge capacity is 135 mAh g -1 , there is basically no capacity decay, and the discharge capacity after 10,000 cycles is 120mAhg -1 , compared with the highest capacity, the capacity retention rate can still reach 89%. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the mass spectrum of H2BCPP in Example 1.
[0019] Figure 2 This is the infrared image of H2BCPP and H2BCPP-COP in Example 1.
[0020] Figure 3 This is the cyclic voltammetry curve of the H2BCPP-COP cathode material in Example 1, with a scan rate of 0.1 mV / s.
[0021] Figure 4 It is the charge and discharge curve of the H2BCPP-COP positive electrode material in Example 1 within the voltage range of 1.6-4.5V.
[0022] Figure 5 This is the long cycle diagram of the positive electrode materials H2BCPP and H2BCPP-COP in Example 1 within the voltage range of 1.6-4.5V.
[0023] Figure 6 This is the long cycle diagram of the positive electrode material H2BCTP in Example 2 within the voltage range of 1.8-4.5V.
[0024] Figure 7 This is the long cycle diagram of the positive electrode material H2BCTP-COP in Example 2 within the voltage range of 1.8-4.5V. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods, but the application and extension of the present invention are not limited.
[0026] Example 1
[0027]
[0028] (1) Synthesis of the intermediate with chemical formula a:
[0029] After degassing 2.4 g (80 mmol) of formaldehyde and 30 mL (400 mmol) of pyrrole with argon, and then passing argon protection, the mixture was cooled to 0°C, 0.1 mL of CF3COOH was added and stirred for 40 min, and then NaOH aqueous solution was added and stirred for 30 min to stop the reaction. The reactants were extracted (V 去离子水 :V 二氯甲烷 = 1:1) and then purified by column chromatography (silica gel powder, V 石油醚 :V 二氯甲烷 = 3:1), and concentrated under reduced pressure to obtain a pure white solid (4.440 g, yield 38%).
[0030] (2) Synthesis of the intermediate with chemical formula b:
[0031] Compound a (2 g, 13.69 mmol) and 4-cyanobenzaldehyde (1.79 g, 13.69 mmol) were added to 500 mL of dichloromethane (DCM), and the mixture was degassed with argon at 0 °C. Boron trifluoride etherate (0.1 mL) was added, and the reaction was stirred for 30 min. 2,3-Dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) (3.1 g, 13.69 mmol) was then added, and the reaction was stirred for 30 min. After the reaction was complete, the mixture was subjected to short column chromatography on silica gel powder (DCM). The liquid after the column was concentrated under reduced pressure, and the residue was purified again by short column chromatography (V 石油醚 :V 二氯甲烷 = 1:4). After recrystallization, a dark purple solid b (448 mg, yield 6.4%) was obtained.
[0032] Its mass spectrum is as follows Figure 1As shown, the successful synthesis of H2BCPP is demonstrated.
[0033] (3) Synthesis of the intermediate with chemical formula C:
[0034] At 0 ° C, compound b (100 mg, 0.195 mmol) and 2.5 mL of dichloromethane (DCM) were added to a 10 ml reaction bottle and mixed, and 2.5 g of trifluoromethanesulfonic acid (TfOH, 99%) was slowly added dropwise. The reaction bottle was frozen with liquid nitrogen and repeatedly evacuated by argon. After melting at room temperature, the reactants were transferred to an oil bath and reacted at 55 ° C for 72 hours. At the end of the polymerization, excess ammonia water was added to neutralize the acid. The obtained dark red solid was ultrasonically cleaned with chloroform, acetone, water and ethanol in an ultrasonicator, and the precipitate was collected by filtration, and then filtered and dried overnight under vacuum at 110 ° C to obtain a dark red solid H2BCPP-COP (84 mg, yield 84%).
[0035] Its infrared image is as follows Figure 2 As shown, 2227cm -1 The characteristic absorption peak of cyano group disappears at 1460cm -1 C=N and 1320cm -1 The characteristic absorption peak belonging to CN was enhanced, indicating that the cyano group underwent polymerization reaction under the catalysis of trifluoromethanesulfonic acid to generate a triazine ring, that is, H2BCPP-COP was successfully synthesized.
[0036] Example 2
[0037]
[0038] (1) Synthesis of the intermediate with chemical formula a:
[0039] After degassing 2.4 g (80 mmol) of formaldehyde and 30 mL (400 mmol) of pyrrole with argon, and then passing argon protection, the mixture was cooled to 0°C, 0.1 mL of CF3COOH was added and stirred for 40 min, and then NaOH aqueous solution was added and stirred for 30 min to stop the reaction. The reactants were extracted (V 去离子水 :V 二氯甲烷 = 1:1) and then purified by column chromatography (silica gel powder, V 石油醚 :V 二氯甲烷 = 3:1), and concentrated under reduced pressure to obtain a pure white solid (4.440 g, yield 38%).
[0040] (2) Synthesis of the intermediate with chemical formula b:
[0041] Compound a (2 g, 13.69 mmol) and 5-cyanothiophenecarboxaldehyde (1.88 g, 13.69 mmol) were added to 500 mL of dichloromethane (DCM), and the mixture was degassed with argon at 0 °C. Boron trifluoride etherate (0.1 mL) was added, and the reaction was stirred for 30 minutes. 2,3-Dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) (3.1 g, 13.69 mmol) was then added, and the reaction was stirred for 30 minutes. After the reaction was completed, the mixture was passed through a short column chromatography on silica gel powder (DCM). After the column, the liquid was concentrated under reduced pressure, and the residue was purified again by short column chromatography (petroleum ether: DCM = 1:3). After recrystallization, a dark purple solid b (800 mg, 11%) was obtained.
[0042] (3) Synthesis of the intermediate with chemical formula C:
[0043] At 0°C, compound b (50 mg, 0.095 mmol) and 10 mL of dichloromethane (DCM) were added to a 50 ml reaction bottle and mixed. After degassing with argon, argon was introduced and 1.2 g of trifluoromethanesulfonic acid (TfOH, 99%) was slowly added dropwise. The reactants were transferred to an oil bath and reacted at 55°C for 5 hours. The solution became viscous and excess ammonia was added to neutralize the acid and terminate the reaction. The obtained purple-black solid was ultrasonically cleaned with chloroform, acetone, water and ethanol in an ultrasonicator, and the precipitate was collected by filtration, and then filtered and dried overnight under vacuum at 110°C to obtain purple-black solid H2BCTP-COP (35 mg, yield 70%).
[0044] The porphyrin monomer and the porphyrin conjugated organic polymer prepared in Example 1 and Example 2 are used as positive electrode active materials for lithium ion batteries, as follows:
[0045] (1) Dissolve 5 parts by weight of H2BCPP and H2BCPP-COP, 4 parts of conductive agent acetylene black, and 1 part of binder polyvinylidene fluoride in N-methylpyrrolidone (10 mg / ml), grind thoroughly, and apply the evenly ground slurry on aluminum foil. Dry the solvent in a vacuum drying oven at 80°C to use as the positive electrode of the battery. The metal lithium sheet is used as the negative electrode, the electrolyte is 1 mol / L LiPF6, and its solvent molecule is PC. The button battery is assembled in an argon atmosphere, and the electrochemical performance is tested in the range of 1.6-4.5V using a constant current charge and discharge instrument at 0.1A g -1 After 20 cycles of activation, the current density was changed to 2.0 A g -1 The electrochemical performance was tested with a current density.
[0046] like Figure 5 As shown, at 2A g -1At the current density of 1.5, the discharge capacity of H2BCPP in Example 1 was 65 mAh g after 600 cycles. -1 After 7500 cycles, the discharge capacity is 83 mAh g -1 The H2BCPP-COP used in the present invention has a discharge capacity of 92 mAh g after 600 cycles. -1 After 7500 cycles, the discharge capacity is 135 mAh g -1 The discharge capacity has basically not decayed, and the discharge capacity is 120mAh g after 10,000 cycles. -1 , compared with the highest capacity retention rate is still 89%.
[0047] (2) Dissolve 5 parts by weight of H2BCTP, 4 parts of conductive agent acetylene black, and 1 part of binder polyvinylidene fluoride in N-methylpyrrolidone (10 mg / ml), grind thoroughly, and apply the evenly ground slurry on aluminum foil. Dry the solvent in a vacuum drying oven at 80°C and use it as the positive electrode of the battery. The metal lithium sheet is used as the negative electrode, the electrolyte is 1 mol / L LiPF6, and its solvent molecule is PC. Assemble it into a button cell in an argon atmosphere, and test the electrochemical performance in the range of 1.8-4.5V using a constant current charge and discharge instrument. -1 After 20 cycles of activation, the current density was changed to 2.0 A g -1 The electrochemical performance was tested with a current density.
[0048] like Figure 6 As shown, at 2A g -1 At the current density of 2, the discharge capacity of H2BCTP in Example 2 was 83 mAh g after 1000 cycles. -1 The capacity retention rate is 90%, and the discharge capacity after 5300 cycles is 63 mAh g -1 , capacity retention rate 75%.
[0049] (3) Dissolve 5 parts by weight of H2BCTP-COP, 4 parts of conductive agent acetylene black, and 1 part of binder polyvinylidene fluoride in N-methylpyrrolidone (10 mg / ml), grind thoroughly, and apply the evenly ground slurry on aluminum foil. Dry the solvent in a vacuum drying oven at 80°C and use it as the positive electrode of the battery. The metal lithium sheet is used as the negative electrode, the electrolyte is 1 mol / L LiPF6, and its solvent molecule is PC. Assemble it into a button cell under argon atmosphere, and test the electrochemical performance in the range of 1.8-4.5V using a constant current charge and discharge instrument. -1 The electrochemical performance was directly tested at a current density of 1.
[0050] like Figure 7 As shown, at 5A g -1At the current density, the H2BCTP-COP used in the present invention has a discharge capacity of 106 mAh g after 1000 cycles. -1 The capacity retention rate is 99%, and the discharge capacity after 3000 cycles is 98 mAh g -1 The capacity retention rate is 92%, and the discharge capacity after 5300 cycles is 94 mAh g -1 , the capacity retention rate is still 88%.
Claims
1. Application of a porphyrin conjugated organic polymer in a lithium ion battery, characterized in that: The porphyrin conjugated organic polymer is used as the positive electrode active material, and is fully and evenly ground with a conductive agent and a binder in a solvent to obtain a positive electrode slurry, which is then applied to a current collector, vacuum dried as a positive electrode, and then assembled into a battery with a negative electrode, an electrolyte, and a separator in an argon atmosphere, wherein the negative electrode is a metal lithium sheet; The general structural formula of the porphyrin conjugated organic polymer is shown in formula (I): Formula (I) Wherein, Ar is selected from , , One of: X is selected from O, N, S; the degree of polymerization n ranges from 8 to 2000.
2. The use according to claim 1, characterized in that: The content of the porphyrin conjugated organic polymer in the positive electrode slurry is 40-90wt%, the content of the conductive agent is 5-60wt%, and the content of the binder is 5-10wt%.
3. The use according to claim 1, characterized in that: The conductive agent is one of conductive graphite, conductive carbon black, carbon nanotubes and graphene; the binder is one of polytetrafluoroethylene, sodium carboxymethyl cellulose, polyvinylidene fluoride and polyurethane; the solvent is N-methylpyrrolidone; and the current collector is one of stainless steel foil, molybdenum foil, aluminum foil, copper foil and nickel foil.
4. The use according to claim 1, characterized in that: The electrolyte is one of LiPF6, LiTFSI, LiFSI, LiClO4, and LiBOB.
Citation Information
Patent Citations
Porphyrin polymer and preparation method and application thereof in positive electrode material
CN110964179A
Sulfurized porphyrin-based covalent triazine composite positive electrode material and preparation method and application thereof
CN115425186A